2022
DOI: 10.3389/fmed.2022.979373
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid CD169/Siglec1: An immunoregulatory biomarker in viral disease

Abstract: CD169, also known as Siglec1 or Sialoadhesin (Sn), is a surface adhesion molecule on human myeloid cells. Being part of the Siglec family, it acts as a receptor for sialylated molecular structures, which are found among various pathogenic and non-pathogenic ligands. Recent data suggest that CD169 may represent a promising new biomarker in acute respiratory and non-respiratory viral infections, such as SARS-CoV-2, Respiratory syncytial virus (RSV) and Human immunodeficiency virus (HIV). Therein lies a great pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In this work, we suggest that the binding of sialoglycoproteins with siglecs would be involved in this process [134] (Figure 4). A variety of other siglec interactions with viral, protozoan pathogens and bacteria have been described elsewhere [135][136][137][138][139]. In 2014, Jandus and colleagues demonstrated that siglec 7 exerts an essential function in tumor escape by disrupting the functions of natural killer cells [129].…”
Section: Siglecsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we suggest that the binding of sialoglycoproteins with siglecs would be involved in this process [134] (Figure 4). A variety of other siglec interactions with viral, protozoan pathogens and bacteria have been described elsewhere [135][136][137][138][139]. In 2014, Jandus and colleagues demonstrated that siglec 7 exerts an essential function in tumor escape by disrupting the functions of natural killer cells [129].…”
Section: Siglecsmentioning
confidence: 99%
“…In this work, we suggest that the binding of sialoglycoproteins with siglecs would be involved in this process [134] (Figure 4). A variety of other siglec interactions with viral, protozoan pathogens and bacteria have been described elsewhere [135][136][137][138][139]. Thanks to advances in the field of glycoimmunology, today we know many siglec genes and binding specificities are quickly evolving among primates, with crucial extant polymorphisms in human populations that may impact vulnerability to infectionassociated disorders [135].…”
Section: Siglecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the carbohydrate binding properties and expression patterns of Sn are well conserved between rodents and humans, where it is expressed by macrophage subsets both under resting and inflammatory conditions [5,6]. Unlike most siglecs, Sn can function as a cellular interaction molecule and mediate trans interactions with ligands on other cells and sialylated pathogens when expressed naturally at the cell surface [7][8][9][10]. In contrast, other siglecs of the immune system are usually masked by cis-interactions with sialic acids co-expressed on the same cell [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the carbohydrate binding properties and expression patterns of Sn are well conserved between rodents and humans, where it is expressed by macrophage subsets both under resting and in ammatory conditions [5,6]. Unlike most siglecs, Sn can function as a cellular interaction molecule and mediate trans interactions with ligands on other cells and sialylated pathogens when expressed naturally at the cell surface [7][8][9][10]. In contrast, other siglecs of the immune system are usually masked by cis-interactions with sialic acids co-expressed on the same cell [4,11].…”
Section: Introductionmentioning
confidence: 99%